Student and teacher co-agency when combining CT with arts and design in a cross-curricular project - Mannila Linda; Leinonen Teemu; Bauters Merja; Veermans Marjaana (ELSEVIER, 2025)
The technological development has raised awareness for the importance of digital competence and computa-tional thinking (CT) to understand the digital world and has resulted in revised curricula in many countries. In Finland, a new curriculum for grades 1-9 came into force in 2016 introducing digital competence (including programming) to be integrated in other subjects. Most teachers lack prior experience in programming and there is a need for suitable instructional models. This article presents a cross-curricular teaching sequence and the results from a case study conducted in four Finnish schools. Students in grades 4-6 collaboratively worked on a project combining arts, design and CT with other subjects. The results show that students demonstrated several CT abilities while working on their projects, in particular creativity, tinkering and debugging. The findings also indicate that teachers and students learned together (co-agency) and suggest that models like the teaching sequence can help and encourage teachers to integrate programming and CT in a cross-curricular manner. Still, the teachers' knowledge, ambition level and understanding of the task at hand, as well as the organizational support appear to play a notable role when planning and carrying out projects of this kind. While CT is commonly seen as developed through programming, the teaching sequence seems to have fostered CT abilities through the project as a whole, with programming playing the role of a tool or a glue depending on the time available, and the students' skill and ambition level.